2013
DOI: 10.1590/s0073-47212013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Trophic relationships between macroinvertebrates and fish in a pampean lowland stream (Argentina)

Abstract: ABSTRACT. The diet and trophic relationships between the macroinvertebrates Phyllogomphoides joaquini Rodrigues Capítulo, 1992 and Coenagrionidae (Odonata), Chironomidae (Diptera), Diplodon delodontus (Lamarck, 1919) (Bivalvia: Hyriidae), and Pomacea canaliculata (Lamarck, 1822) (Gastropoda: Ampulariidae) and the fishes Pimelodella laticeps Eigenmann, 1917 (Heptapteridae) and Bryconamericus iheringii (Boulenger, 1887) (Characidae) in a temperate lowland lotic system in Argentina were assessed on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
0
11
0
10
Order By: Relevance
“…species, Acanthocyclops robustus lives mainly in the limnetic zones of large ponds and lakes (Dussart & Fernando 1990); Ectocyclops phaleratus is an uncommon benthic species, inhabiting mainly the littoral zone and only occasionally the water column (Dussart, 1969;Reid, 1985); Macrocyclops albidus lives among macrophytes, reaching its maximum development during summer (Pennak 1966); and Tropocyclops prasinus is a common species within the periphytic and benthic communities (Dussart, 1969), in warm waters, tolerating brackish water, and rarely behaving as planktonic (Margalef, 1983). Chironomid larvae and mayfly nymphs, which taxa are common in lotic and lentic Neotropical environments where the food availability is ample (Marchese, 1984;Kaisin, 1989;López van Oosterom et al, 2013), were found in the diet of P. laticeps at high frequencies during spring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…species, Acanthocyclops robustus lives mainly in the limnetic zones of large ponds and lakes (Dussart & Fernando 1990); Ectocyclops phaleratus is an uncommon benthic species, inhabiting mainly the littoral zone and only occasionally the water column (Dussart, 1969;Reid, 1985); Macrocyclops albidus lives among macrophytes, reaching its maximum development during summer (Pennak 1966); and Tropocyclops prasinus is a common species within the periphytic and benthic communities (Dussart, 1969), in warm waters, tolerating brackish water, and rarely behaving as planktonic (Margalef, 1983). Chironomid larvae and mayfly nymphs, which taxa are common in lotic and lentic Neotropical environments where the food availability is ample (Marchese, 1984;Kaisin, 1989;López van Oosterom et al, 2013), were found in the diet of P. laticeps at high frequencies during spring.…”
Section: Discussionmentioning
confidence: 99%
“…Almirón et al (2000) and López van Oosterom et al (2013) remarked that P. laticeps is a permanent species in the El Pescado Stream because of the fish ecologic plasticity facing the marked instability of habitat. Colautti et al (2009) noted that the species is also permanent in the La Choza Stream; whereas Paracampo (2012) recorded the catfish as a semipermanent species in El Pescado Stream.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral materials were also recorded in the stomach contents of P. canaliculata, but it is unknown whether they were part of the grit present in the gizzard that is used for triturating food (Andrews, 1965), or they were incorporated by scraping during the ingestion, taking into account that the stream studied presents a high content of fine sediment in the stream bottom (Ocon et al, 2013;López-van Oosterom et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The streambed of the Pampean streams is composed of fine sediments (clay and silt) that are colonized by an epipelic biofilm in which diatoms are the dominant group, A c c e p t e d M a n u s c r i p t constituting the basal trophic levels for extensive food webs Ocón et al, 2013). These streams show a relatively high concentration of nutrients when they are compared with other lotic systems of the world (Bauer et al, 2002, Giorgi et al, 2005, and can be classified as eutrophic when phosphorus is considered, or as mesotrophic when nitrogen is taken into account (Feijó & Lombardo, 2007).…”
Section: Introductionmentioning
confidence: 99%